AUTOMATED MILK PRESERVATION SYSTEM USING FUZZY LOGIC SYSTEM - S. Yasmeen; M. S. Khan (Journal of Animal and Plant Sciences, 2013)
In this paper Automated Milk Preservation System has been discussed using fuzzy logic system. The basic idea of the research is to make theUltra-high temperature processing (UHT) Treated Milk Preservation systems automated by applying rule base of fuzzy logic. In this system three input variables were considered for three types of milk: Skim Milk, Full Cream Milk and Low Cream Milk. According to the required type of milk the nine output variables were designed to fulfill the requirements. The output variables: Valve opening time for skim milk, Valve opening time for low cream milk, Valve opening time for full cream milk, Processing time of skim milk, Processing time of low cream milk, Processing time of full cream milk, Heating/cooling time for skim milk, Heating/cooling time for low cream milk, and Heating/cooling time for full cream milk were considered. The system is developed using MATLAB Simulink R2011a. The results obtained from simulation were according to the design values.
Keywords: Fuzzy Logic System; UHT Treated Systems; Skim Milk; Full Cream Milk; Low Cream Milk; Milk Preservation Systems